(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
The article is devoted to the competence of using modern and virtual distance solutions for the professional growth of a teacher, improving his/her pedagogical skills. The availability of various educational resources for biology teachers to attract new pedagogical tools directly forms a digital educational environment. The features of using distance online platforms to improve the qualifications of teachers and improve the educational process, the possibility of providing tutoring assistance to teachers are considered. Information is provided on the creation of a modern information and educational environment and the use of technologies to improve continuity, consistency, scientific literacy in the field of pedagogical education for general secondary education institutions, the organization and management of the educational process at a high level, and increasing the effectiveness of training biology teachers.